Effect of diameter and log shape on the veneer recovery rate in a plywood plant / Wan Mohd Nazri Wan Abdul Rahman and Mohd Ariff Jamaludin - Wan Abdul Rahman, Wan Mohd Nazri; Jamaludin, Mohd Ariff (2004)
Wood veneer is the main input for plywood manufacture and plywood is a value added product of veneer. A study to determine the recovery rate of logs that was to be converted into plywood was done at a local factory in Kuala Terengganu, Terengganu. The objectives of the research was to determine the effect of diameter and log shape on the recovery rate in five early stages of the veneer production line. The five stages of veneer preparation studied were logyard/deck, debarker, rotary lathe, dryer and core builder/composer. The results showed that the recovery rate cf logs with a diameter above 50 cm was 58.81% and diameter below 50 cm was 55.98 percent. The difference as observed in the analysis was not significant. On the other hand, the recovery rate for log shape factor for straight logs were 62.83% and curved logs were 51.96 percent. Tills showed that the log shape factor significantly affected recovery rate. When analysed based on the diameter, it is concluded that diameters above 50 cm generated a higher recovery rate than diameters below 50 cm. In terms of production based on the diameter, it was indicated in this study that the diameter did not influenced significantly the veneer recovery, although there was a trend that larger log diameter resulted in higher veneer output. The difference as observed in the analysis was not significant at the 0.05 percent significant level. Tills study confirms the general believe that higher percentage veneer recovery is attainable with straight log shape than curved log. Higher percentage veneer recovery was attained by straight logs than curve Jog. The straight logs were easier to handle by the machines such as peeling by the rotary lathe during the initial stages.